The Utilization of Solid Waste of Tea as The Growth Media of TANAMAN SELADA (Lactuca sativa - Rosdiana, Rosdiana; Gustia, Helfi; Rifaldi, Ach (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
The purpose of the study was to respond to the growth of mustard greens on the composite media of tea waste and soil. Completely randomized block design was used in the study with 6 treatments and 4 groups/replication, where one experimental unit consisted of 3 plants. The six treatments were: 1) 2000g soil media (P0), 2) 1000g soil composite media + 1000g cow manure (P1), 3) the composite media of tea waste (100g) and soil (1900g) (P2), 4) the composite media of tea waste (200g) and soil (1800g) (P3), 5) the composite media of tea waste (300g) and soil (1700g) (P4), and 6) the composite media of tea waste (400g) and soil (1600g) (P5). The observed variables were plant height, number of leaves, and root volume. total weight, root weight, consumption weight, and biomass. The results showed that there was no significant difference between treatments on plant height growth, number of leaves, total weight, roots weight, and consumption weight. The treatment of growing media gave a significant difference to the biomass of whole plant, roots, consumption and the volume of roots. The composite media of tea waste (100 g) and soil (1900 g) gave the highest value on the biomass of whole, roots, consumption and the root volume.